2012
DOI: 10.1177/1084822312465747
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of a Statewide Initiative to Enhance Depression Care Among Older Home Care Patients

Abstract: Late-life depression is prevalent in home care. This pilot study, part of a statewide initiative to enhance depression care, evaluated the influence of a 2-hour depression screening and intervention workshop on home care professionals' knowledge, self-efficacy, and attitudes related to depression in older home care patients. A pretest, posttest design was used to evaluate the effects of the workshop with 280 home care professionals from 7 home care agencies. Following the depression workshop, participants' kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…It was unclear who intervention deliverers were in 12 studies (21.8%) [26, 39, 46, 50, 51, 55, 5964], but in studies where this information was identifiable, deliverers were most frequently nurses (10 studies, 18.2%) [33, 3537, 40, 47, 52, 6567]. With regards to level and mode of delivery, interventions were most frequently delivered at the individual (25 studies, 45.5%) [2729, 33, 34, 40, 41, 45, 46, 48, 50–52, 54, 56, 60, 63, 65, 66, 6873] and group level (19 studies, 35.1%) [26, 31, 32, 38, 39, 42, 43, 49, 53, 55, 58, 61, 62, 64, 67, 7477]. Face to face was the most common (28 studies, 50.9%) mode of delivery [27, 29, 31, 32, 3538, 4145, 49, 50, 56, 58, 6062, 6668, 7478].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was unclear who intervention deliverers were in 12 studies (21.8%) [26, 39, 46, 50, 51, 55, 5964], but in studies where this information was identifiable, deliverers were most frequently nurses (10 studies, 18.2%) [33, 3537, 40, 47, 52, 6567]. With regards to level and mode of delivery, interventions were most frequently delivered at the individual (25 studies, 45.5%) [2729, 33, 34, 40, 41, 45, 46, 48, 50–52, 54, 56, 60, 63, 65, 66, 6873] and group level (19 studies, 35.1%) [26, 31, 32, 38, 39, 42, 43, 49, 53, 55, 58, 61, 62, 64, 67, 7477]. Face to face was the most common (28 studies, 50.9%) mode of delivery [27, 29, 31, 32, 3538, 4145, 49, 50, 56, 58, 6062, 6668, 7478].…”
Section: Resultsmentioning
confidence: 99%
“…An assessment of participants’ understanding was included in 20 (60.6%) studies [25, 29, 31, 3337, 39, 45, 47, 48, 50, 57, 61, 65, 67, 73, 75, 78] and an assessment of participants’ performance of intervention-related skills in 14 (42.4%) studies [3336, 45, 47, 48, 51, 54, 56, 57, 65, 75, 78]. With regards to strategies to enhance receipt, 4 (12.1%) studies reported using a strategy to enhance participants’ understanding [41, 48, 56, 57], 7 (21.1%) to enhance performance of intervention-related skills [39, 41, 44, 47, 48, 56, 57].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations